Students’ Motivation of Senior High School in Learning Foreign Language - Ani Latifah; Zulaiha Zulaiha; Shanshan Xu; Amina Intes; Uwe Barroso (Yayasan Adra Karima Hubbi, 2023)
Background. One of the foreign languages that has always been studied in Indonesia is English. In fact, English is one of the subjects that must be tested during the national exam. Purpose. The purpose of the study explored students' motivation in learning English by administering questionnaires and conducting interviews. The respondents consisted of 33 participants. Method. Data was obtained by giving teacher performance scales, teacher digital literacy, and online learning implementation scales. Results. Interviews were given to some students and teachers. The study found that the majority of students had good integrative motivation in learning English. This is followed by instrumental motivation, which relates to their goals in learning English. However, students' good instrumental motivation also does not affect students' achievement or learning outcomes. Conclusion. This is due to external factors or the students' environment in their daily lives.